On twinning and anisotropy in rolled Mg alloy AZ31 under uniaxial compression. (July 2015) - Guo, X.Q.; Chapuis, A.; Wu, P.D.; Agnew, S.R.
Abstract: The mechanical anisotropy of hot-rolled Mg alloy AZ31 is investigated both experimentally and numerically. First, five different specimen orientations with tilt angles of α = 0°, 30°, 45°, 60° and 90° between the normal direction and longitudinal specimen axis are used to experimentally study the mechanical anisotropy under uniaxial compression. Then, the Elastic Visco-Plastic Self-Consistent (EVPSC) model, with the recently developed Twinning and De-Twinning (TDT) description, is applied to simulate the uniaxial compression tests. It is demonstrated that accounting for the initial texture and calibrating the EVPSC-TDT model using in-plane uniaxial tension and compression along the rolling direction permits prediction of the strength anisotropy and strain hardening behavior along all the five orientations, for cases in which the contribution of twinning is dominated, negligible and intermediate.